THE DOUBLEBASS: HISTORY AND CONTEMPORANEITY - SOCICAN, IGOR (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2022)
The author aims to outline a broad picture of the historical developments of the double bass, an instrument rooted in the rich medieval European tradition of building stringed instruments. The early forms of the double bass, the terminology, the tunings are presented, the role of the instrument in the instrumental formations and the establishment of its place in the classical symphony orchestra are appreciated. An important repertoire for double bass is reviewed, the composers who approached its sonority, are presented the most famous performers, representatives of different schools and directions of interpretation. The author talks about the importance of knowing all these aspects for research and evaluation of the role of this instrument in contemporary music